Neurovascular photoacoustic tomography - Hu, Song; Wang, Lihong V. (Frontiers in Neuroenergetics, 2010)
Neurovascular coupling refers to the relationship between neuronal activities and downstream hemodynamic responses. Photoacoustic tomography (PAT), enabling comprehensive label-free imaging of hemodynamic activities with highly scalable penetration and spatial resolution, has great potential in the study of neurovascular coupling. In this review, we first introduce the technical basis of hemodynamic PAT—including label-free quantification of total hemoglobin concentration, blood oxygenation, and blood flow—as well as its applications in hemodynamic monitoring. Then, we demonstrate the potential application of PAT in neurovascular imaging by highlighting representative studies on cerebral vascular responses to whisker stimulation and Alzheimer’s disease. Finally, potential research directions and associated technical challenges are discussed.